High-vs medium-frequency neuromuscular electrical stimulation protocols on muscle mass in Intensive Care Unit patients, a pilot study - Georgopoulos, Christos; Katsogianni, Aikaterini; Patsaki, Eirini; Sidiras, Georgios; Vasileiadis, Ioannis; Magira, Eleni; Nanas, Serafim; Karatzanos, Lefteris (Health & Research Journal, 2023)
Aim: The aim of the present study was to investigate whether a high-frequency (HF) neuromuscular electrical stimulation (NMES) protocol could result in a smaller loss of muscle mass than a moderate-frequency (MF) protocol in ICU patients. Methods and materials: In this randomized pilot control trial, patients of the two intervention groups followed daily NMES sessions from the day of ICU admission until the tenth day. All study groups received physiotherapy in terms of usual care. Muscle layer thickness was assessed with ultrasound in the vastusintermedius (VI) and rectus femoris (RF) muscle to evaluate changes in muscle mass. Results: Totally 58 patients were allocated into three groups and 29 were finally analyzed (control: 10, MF: 12, HF: 7). Significant differences (p=0.05) between control and pooled NMES groups were observed for the right RF and VI. Significant differences in favor of HF vs MF group were observed for the left RF (3.6±15.3 vs 7.2±7.9% respectively, p=0.04). No differences were found regarding the number of sessions and presence of oedema (p>0.05), while strength of contraction during sessions tended to be somewhat higher in the HF (p=0.09). Conclusion: HF may be more effective than MF to prevent muscle mass loss in ICU patients. More studies are needed to determine the optimal NMES characteristics.